Introduction of Project Management in Activity of Authorities of the Region as the Mechanism of Increase in its Investment Appeal - Azamat Borisovich Tlisov; Natalia Nikolaevna Kiseleva (Управленческое консультирование)
In article the retrospective analysis of introduction of design approach is presented to activity of public authorities, the best practicians of project management in regions of the Russian Federation are described, the interrelation between the level of development of project management in regional authorities and a condition of investment climate of regions is revealed. Authors consider key problems of introduction of project management in activity of executive authorities of subjects of the Russian Federation. Among them special attention is paid to a problem of a mismatch of documents of strategic planning, programming and projects, lack of a clear idea of organizational structure of management of design activity in authorities of regions, to the difficulties connected with shortage of competences in design management at executives and participants of projects, backwardness of system of motivations of participants of the project, considerable differentiation of regions on quality of standard and methodical maintenance of process of introduction of project management in activity of executive authorities of territorial subjects of the federation.